MORPHOLOGICAL, ANATOMICAL AND GEOGRAPHICAL DISTRIBUTION STUDIES OF SPECIES Horwoodia dicksoniae (Turrill) IN IRAQ - Al-Masoudi, R. K. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aims to study the morphological anatomical characteristics and geographical distribution of the species Horwoodia dicksoniae (Turrill) belong to Brassicaceae family in Iraq. The results were revealed the morphological characteristics of the root, stem, leaves, fruits and seeds, abaxial surface of the leaf characterized by covered with simple hairs. The fruits were circular in shape with wide wing and have one seed. The seeds were conical shape and pustular surface configuration. The anatomical characteristics of the root, stem, and leaf were studied and the cross-section of the root was characterized by thick periderm layer and cortex layer consisting primarily of parenchyma cells, stem cross section was characterized by thick layer of cuticle, as well as epidermis layer that followed the cuticle layer was double epidermis, but the layer of phloem is composed of rectangular cells and arranged in a continuous ring. Cross section of leaf was bifacial , leaf contains palisade cells in the form of a rectangle at the top surface of the leaf and irregular spongy cells at the low surface and distinguish the middle vein of the leaf as a circular shape. The epidermis was characterized by an Anisocytic type. The study of geographical distribution has been shown that the species is widespread in the desert region of Iraq.